"A fly appeared": sable, a classic Drosophila mutation, maps to Yippee, a gene affecting body color, wings, and bristles. Issue 5 (10th March 2022) - Dean, Derek M; Deitcher, David L; Paster, Caleigh O; Xu, Manting; Loehlin, David W
Abstract: Insect body color is an easily assessed and visually engaging trait that is informative on a broad range of topics including speciation, biomaterial science, and ecdysis. Mutants of the fruit fly Drosophila melanogaster have been an integral part of body color research for more than a century. As a result of this long tenure, backlogs of body color mutations have remained unmapped to their genes, all while their strains have been dutifully maintained, used for recombination mapping, and part of genetics education. Stemming from a lesson plan in our undergraduate genetics class, we have mapped sable 1, a dark body mutation originally described by Morgan and Bridges, to Yippee, a gene encoding a predicted member of the E3 ubiquitin ligase complex. Deficiency/duplication mapping, genetic rescue, DNA and cDNA sequencing, RT-qPCR, and 2 new CRISPR alleles indicated that sable 1 is a hypomorphic Yippee mutation due to an mdg4 element insertion in the Yippee 5′-UTR. Further analysis revealed additional Yippee mutant phenotypes including curved wings, ectopic/missing bristles, delayed development, and failed adult emergence. RNAi of Yippee in the ectoderm phenocopied sable body color and most other Yippee phenotypes. Although Yippee remains functionally uncharacterized, the results presented here suggest possible connections between melanin biosynthesis, copper homeostasis, and Notch/Delta signaling; in addition, they provide insight into past studies of sable cell nonautonomy and of the genetic modifier suppressor of sable .